The wine market in China: sounding board for the ups and downs of the international order - Gualda, Lucas (2025)
Wine in China is a rising industry, to the extent that the country is achieving significant international representation. Commercially, it is also gaining importance as a major importer, especially of luxury wines, which gives it leverage to impose sanctions on exporting countries or regions. Much like the electric vehicle industry, viticulture has become another instrument of Chinese soft power, with the additional feature that it is developing in remote regions such as Ningxia, Yunnan, and Xinjiang. This article reviews the general aspects of the development of wine in China, describes the country’s role as an importer, and analyzes its implications for international politics.